Case Report: Suspected Case of Brucella-Associated Immune Reconstitution Inflammatory Syndrome - Qu, Chunmei; Xu, Nannan; Niu, Dehong; Wen, Sai; Yang, Hui; Wang, Shanshan; Wang, Gang (Frontiers in Immunology, 2022)
Human brucellosis is one of the most prevalent zoonoses. There are many similarities between the pathogenesis of Mycobacterium tuberculosis (MTB) infection and that of brucellosis. Immune reconstitution inflammatory syndrome (IRIS) may occur during the treatment of MTB infection, but it has not been reported in brucellosis cases thus far. We report the case of a 40-year-old male whose condition initially improved after adequate anti-Brucella therapy. However, three weeks later, the patient presented with exacerbation of symptoms and the development of a paravertebral abscess. After exclusion of other possible causes of clinical deterioration, IRIS with brucellosis was presumed. After supplementation with anti-Brucella treatment with corticosteroids, the abscess disappeared, and the symptoms completely resolved. Our case suggests that it is necessary to be aware of the possible occurrence of IRIS in patients with brucellosis in clinical practice.